Silencing HIF-1α aggravates growth inhibition and necrosis of proximal renal tubular epithelial cell under hypoxia. (25th November 2016) - Chen, Yue; Jiang, Suhua; Zou, Jianzhou; Zhong, Yihong; Ding, Xiaoqiang
Abstract: The kidney is particularly susceptible to ischemia/hypoxia insult while dysfunction of proximal tubular epithelial cells (PTEC) is a primary pathologic hallmark in acute kidney injury. Hypoxia-inducible factor-1 (HIF-1) is a key regulator responsible for cellular hypoxic responses. Therefore, we investigated the effects of HIF-1 suppression, using small interference RNA (siRNA), upon the cell fate of PTEC under hypoxia, and explored the underlying possible molecular mechanism. Hypoxia was induced with hypoxia mimetic cobalt chloride. Our data showed that, in HIF-1α siRNA group, the HK-2 cells growth inhibition and necrosis became worse than those in hypoxia group. However, for apoptosis, no significant difference was observed between them. Consistent with the downregulation of HIF-1α in HIF-1α siRNA group, both mRNA and protein expression of glucose transporter-1 (Glut-1) and vascular endothelial growth factor (VEGF) also reduced more significantly than those in hypoxia group. In conclusion, silencing HIF-1α gene could aggravate growth inhibition and necrosis of PTEC under hypoxia. We provide evidence, from the opposite direction, that HIF-1 activation under hypoxia may facilitate adaptation and survival of proximal renal tubular cells, and the beneficial effects may be related to its downstream genes, such as Glut-1 and VEGF.